(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted in Babylon province in the period from August 2019 to February 2020. The CSF specimens (94) were collected with an age range of 14 days to 6 years from Babylon Hospital for Women and Children and Al-Zahra Hospital in AL-Najaf (Microbiology unit). The specimens were generally collected from patients clinically diagnosed by specialist physicians from each suspected child with meningitis from a lumbar puncture by pricking the lumbar puncture in an amount of cerebrospinal fluid divided into two tubes; the first is a cytological and bacteriological examination, and the second tube is subjected to biochemical tests. Results showed lymphocyte increased at 47.9%, compared to neutrophil at 4.2% and lymphocyte with neutrophil percentage at 27.7%. It was also observed that most of the samples are high in protein and natural sugar at 92% compared to high protein and low sugar at 8%. E. coli is the most diagnosed bacteria at 4.2%, followed by Streptococcus pneumoniae at 2.1%. The most common diagnosed virus is Enterovirus at 41.4 %, followed by Varicella zoster virus at 1.1% and then Human Herpes virus 6 at 1.1%.